(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
A behavioral group therapy for patients with chronic orofacial pain is presented. Going beyond the idea of a psychological support-group for pain-sufferers, an effort of behavioral change is proposed, based on a complex model in which physiological and psychological aspects interact. Applied behavior analysis and cognitive behavior therapy are two approaches that sustain the construction of group therapies on a learning format for the acquisition of better ways to cope with pain. Clinical behavior analysis tries, starting from a functional analysis of the psychotherapy process, to come to profoundly curative changes. The junction of the two (the learning format and the functional analytic psychotherapy) happens when during the sessions, verbal episodes are not understood as exchanges of information but analyses as acts in context.